Pemanfaatan Eco-Enzyme sebagai Koagulan dan Pupuk Ramah Lingkungan - Arianti, Miranda Putri; Rachmanto, Tuhu Agung (Jurnal Serambi Engineering, 2025)
Environmental issues related to waste management and the need for sustainable agriculture have driven the search for eco-friendly alternatives. This study explores the utilization of eco-enzyme as a coagulant and organic fertilizer. Eco-enzyme, produced through fruit peel fermentation, was tested for its effectiveness in particle sedimentation in wastewater and enhancing soil fertility. The research employed an experimental approach, using jar test for coagulation and applying eco-enzyme as a liquid fertilizer on plants. Results indicate that eco-enzyme is less effective as a coagulant due to an increase in Total Suspended Solids (TSS) and water turbidity. However, eco-enzyme made from dragon fruit peel (U3) met the liquid organic fertilizer standards with appropriate C, N, P, and K levels, significantly improving soil fertility and plant growth. In conclusion, eco-enzyme has potential as an eco-friendly organic fertilizer but is less effective in coagulation functions.